The contribution of the age distribution of cases to COVID-19 case fatality across countries: a 9-country demographic study - Sudharsanan, Nikkil; Didzun, Oliver; Bärnighausen, Till; Geldsetzer, Pascal (Annals of internal medicine, 2020)
BACKGROUND: There is wide variation in coronavirus disease 2019 (COVID-19) case-fatality rates (CFRs) across countries, leading to uncertainty about the true lethality of the disease. A large part of this variation may be due to the ages of individuals who are tested and identified. - OBJECTIVE: To measure the contribution of distortions from the age distributions of confirmed cases to CFRs within and across populations. - DESIGN: Cross-sectional demographic study using aggregate data on COVID-19 cases and deaths by age. - SETTING: Population-based data from China, France, Germany, Italy, the Netherlands, South Korea, Spain, Switzerland, and the United States. - PARTICIPANTS: All individuals with confirmed COVID-19, as reported by each country as of 19 April 2020 (n = 1 223 261). - MEASUREMENTS: Age-specific COVID-19 CFRs and age-specific population shares by country. - RESULTS: The overall observed CFR varies widely, with the highest rates in Italy (9.3%) and the Netherlands (7.4%) and the lowest rates in South Korea (1.6%) and Germany (0.7%). Adjustment for the age distribution of cases explains 66% of the variation across countries, with a resulting age-standardized median CFR of 1.9%. Among a larger sample of 95 countries, the observed variation in COVID-19 CFRs is 13 times larger than what would be expected on the basis of just differences in the age composition of countries. - LIMITATION: The age-adjusted rates assume that, conditional on age, COVID-19 mortality among diagnosed cases is the same as that among undiagnosed cases and that individuals of all ages are equally susceptible to severe acute respiratory syndrome coronavirus 2 infection. - CONCLUSION: Selective testing and identification of older cases considerably warps estimates of the lethality of COVID-19 within populations and comparisons across countries. Removing age distortions and focusing on differences in age-adjusted case fatality will be essential for accurately comparing countries' performance in caring for patients with COVID-19 and for monitoring the epidemic over time. - PRIMARY FUNDING SOURCE: Alexander von Humboldt Foundation.